A Benthamite Critique of Manne’s Entrepreneurial ‎Defence of Insider Trading: Utility Vs. Reward - Das , Prof (Dr.) Pradip Kumar; Deep, Prabhat; Raghuvanshi , Shivam; Saha, Sohom (International Journal of Accounting and Economics Studies, 2025)
Henry G. Manne’s book, ‘Insider Trading and the Stock Market,’ was the first attempt in the ‎literature to explore the subject thoroughly and present a logical conception as a basis for ‎the development of legal rules on insider Trading. Manne’s theory postulates insider trading as a ‎legitimate reward for entrepreneurs who are ‘organizers of uncertainties’; they combine the ‎thought of productive factors to promote market efficiency. However, this view overlooks the ‎disproportionate harm inflicted on uninformed market participants and the erosion of public ‎trust in financial systems. Bentham’s utilitarianism advocates maximum happiness for the maximum ‎number, and provides a compelling foundation for regulatory intervention through positive law. By ‎emphasizing collective welfare over individual gain, Bentham’s framework supports legal ‎mechanisms that deter insider trading and promote transparency. This qualitative work analyses ‎the tension between individual entrepreneurial benefit and societal harm, arguing that insider ‎trading regulation is ethically justified when viewed through a utilitarian lens. The analysis ‎reveals that while insider gains may be minimal, the aggregate losses to outsiders through ‎distorted prices and reduced confidence are substantial. Bentham’s utility calculus favours ‎regulation as a means to safeguard market integrity and ensure equitable participation. This ‎study contributes to the ongoing discourse on financial ethics and the philosophical ‎underpinnings of securities regulation‎.